Serine-129 phosphorylated α-synuclein drives mitochondrial dysfunction and calcium dysregulation in Parkinson’s disease model - Jie Jiao; Weijin Liu; Weijin Liu; Ge Gao; Hui Yang (Frontiers in Aging Neuroscience)
Phosphorylation of α-synuclein at serine-129 (p-α-syn) is a hallmark of Parkinson’s disease (PD) and constitutes nearly 90% of α-synuclein in Lewy bodies, playing a critical role in disease progression. Despite its pathological significance, the molecular targets and mechanisms driving p-α-syn-induced toxicity, particularly mitochondrial dysfunction, remain poorly understood. In this study, we observed mitochondrial dysfunction in primary cortical neurons derived from mice overexpressing human α-synuclein (h-α-syn), which also exhibit elevated levels of p-α-syn. Notably, inhibiting Ser129 phosphorylation improved mitochondrial function, underscoring the role of p-α-syn in mitochondrial damage. To investigate the molecular mechanism, we performed co-immunoprecipitation (CO-IP) combined with mass spectrometry (MS) to identify p-α-syn binding proteins. This analysis identified protein tyrosine phosphatase interacting protein 51 (PTPIP51) and vesicle-associated membrane protein-associated protein B (VAPB) as key binding partners. Both proteins are localized in the mitochondria-associated endoplasmic reticulum mem-brane (MAM) and essential for calcium transfer between the endoplasmic reticulum (ER) and mitochondria. Our results showed that p-α-syn binds to PTPIP51 and VAPB, disrupting calcium signaling between the ER and mitochondria. Importantly, inhibition of Ser129 phosphorylation partially rescued calcium homeostasis. These findings uncover a novel mechanism by which p-α-syn drives mitochondrial dysfunction and calcium dysregulation through its interactions with MAM-associated proteins, providing new insights into its role in PD pathogenesis and potential therapeutic targets.